Implementasi Strategi Pembelajaran Bahasa Indonesia Pada Materi Teks Puisi Dalam Kurikulum Merdeka di Kelas VIII SMP Negeri 16 Kota Jambi - Muhammad Haikal; Taufik Hidayat Simanjuntak; A. K Farhan; Helty Helty; Liza Septa Wiliyanti (AMI, 2026)
This study aimed to describe the implementation of Indonesian language learning strategies for poetry text materials in the Merdeka Curriculum at Class VIII/I of SMP Negeri 16 Jambi City. This study employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña interactive analysis model, including data reduction, data display, and conclusion drawing. The findings revealed that the learning strategies, particularly discussion and practice, encouraged students to actively participate in analyzing, writing, and presenting poetry. The implementation was supported by interactive learning strategies, students' enthusiasm, and the teacher's classroom management skills. However, several obstacles were identified, including limited learning media and differences in students' self-confidence. To overcome these challenges, the teacher optimized the available learning media, provided motivation, and applied interactive teaching methods. Therefore, the implementation of Indonesian language learning strategies for poetry texts was in accordance with the principles of the Merdeka Curriculum, which emphasizes student-centered learning.